Creative Thinking in the Light of the Behavioral and Creative Economy - Andreev, Rumen (Research Papers, 2017)
The objective of this paper was to prove that in the core of modern economics stayed creative behavior that was not only the result of intellect but also of right lateral thinking, studied by neuroscience. The study of creative behavior required analysis of human thinking, which was the basis for achieving creativity in the economy. The investigation was devoted to the issues of creative thinking, and addressed the main conditions for a creative solution to the economic problems. The necessary elements of creative behavior, methods, and techniques of individual and group creative thinking had been identified. A comparative analysis of different concepts from behavioral economics was performed for the purpose of the study as they were compared with the creative economy paradigms so that creative behavior synthesis could be made. An interdisciplinary approach was used as investigations of intelligence, psychology, and neuroeconomics had been combined and analyzed. However, the already existing publications on behavioral economics in Bulgaria, it had been relatively inadequately known, while the creative economy had been analyzed in terms of the intellectual property. In the economically developed countries creativity became a major economic resource providing crucial competitive advantage. The behavioral and creative economy development enabled the study of creative behavior and the creative thinking in its core, with its results such as innovation, creative products, marketing, entrepreneurship, etc.